Komunikasi Interpersonal Dalam Peningkatan Wawasan Sosial Keagamaan Bagi Pelanggan Kopi Tombo Batang - Ade Gunawan; M. Aris Syafi’i; Afit Ahwaludin (CV. Ulil Albab Corp, 2025)
This study aims to assess the significance of interpersonal communication. in enhancing the social and religious life insights of Kopi Tombo customers in Batang Regency. Coffee shops function as informal public spaces that facilitate social interactions among individuals from various backgrounds. This research employs a qualitative methodology through in-depth interviews, and observations. with customers and the management of Kopi Tombo. The research findings show that interpersonal communication at Kopi Tombo fosters inclusive social discussions, enhances religious understanding, and promotes tolerance. With discussions that take place spontaneously and casually, clients can exchange ideas, share religious experiences, and broaden their social perspectives. This dynamic is supported by the role of the coffee shop manager as a discussion mediator. This study found that Tombo Coffee Shop not only serves as a place to relax but also functions as a social space designed to interact with others and learn about social and religious life. This research can be used as a guide for other public space managers on how to utilize social interactions to enhance harmony and tolerance among individuals.